Desain dan Analisis Pengaruh Parameter PI pada Sistem Kontrol Posisi Prototype Kendaraan Listrik - Yogga Samekto Utomo; Fatkhur Rohman (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2020)
In electric vehicles using autonomous technology, some use gyroscope and accelerometer sensors to determine the vehicle's position. The two sensors work together to detect vehicles by reading the vehicle's position relative to gravity and horizontal and vertical acceleration, and the reading result can help the controller determine which direction the BLDC motor is rotating. However, if there are problems with both sensors, it may cause the program to run incorrectly or the vehicle may not function properly. The results of the conducted studies show that by changing the value of PI, it is possible to change the response of the position control system on the prototype electric vehicle, especially to the parameters of resistance to overshoot and steady-state error. In the rise time stability parameter, changes in the value of the PI constant and changes in the load do not have a significant effect. In this study, the values Kp = 2 and Ki = 18 showed the best results for all values of the system stability parameter. For example, the lowest error value for steady-state error and overshoot, and the most stable rise time value even when the load changes.